UJI EFEKTIVITAS ANALGETIK KOMBINASI EKSTRAK ETANOL DAUN KUMIS KUCING (Orthosiphon stamineus Benth) DAN DAUN SELEDRI (Apium graveolens) TERHADAP MENCIT JANTAN (Mus musculus) - Hardianti, Sitti; Mahdi, Nur; Hamiddani Syaiful, Raisha (Universitas Borneo Lestari, 2024)
Unpleasant sensory and emotional experiences arising from injury or damage to organs are often referred to as pain. Synthetic drugs are often used to treat the pain but often cause harmful side effects. Cat whisker leaves (Orthosiphon stamineus Benth) and celery leaves (Apium graveolens) are often an alternative choice of treatment for pain because they have potential as analgesics. The purpose of this study was to determine the analgesic effect of a combination of ethanol extracts of cat's whiskers and celery leaves on male mice (Mus musculus) using acetic acid as an inducer with a combination dose of 1:1, 1:5 and 5:1. The research is experimental using the writhing test method followed by data analysis including normality, homogeneity, one-way anova and LSD post hoc tests. The results obtained from the study showed that the analgesic effectiveness of the three doses of the combination was greater than the positive control of paracetamol, with a ratio of 2.9 times for combination I, 2.7 times for combination II and the largest comparison was in combination III which was 3 times with the highest percent protection of 74.64%. So it can be concluded that the combination of ethanol extracts of cat whisker leaves and celery leaves has an effect as an analgesic and can inhibit pain better than paracetamol.